Impact of Urbanization and Labor Vulnerability Over the COVID-19 Dynamic Across Countries: A Survival Analysis (Journal of Organizational Psychology, 2021)
This study analyzes the evolution of daily recorded cases of COVID-19 among all countries. In more detail, using survival models, we study the average duration of the increase of cases of COVID-19 before reaching its maximum and reduce the number of infected daily. Additionally, we incorporate dummies to control the levels of urbanization and labor vulnerability as the main control variables. Among the main results, we observed that countries with 50% of the population living in urban areas tend to have more extended periods of infection before reaching their maximum levels and entering a plateau. Besides, the vulnerability variable ends up not being significant by itself. Still, in interaction with the urbanization variable, we observe that countries with high urbanization levels and high levels of vulnerable employment reach the maximum infection level earlier than other countries.
Keywords: organizational psychology; COVID-19, urbanization, labor vulnerability